Enhancing the natural absorbing capacity of rivers to restore their resilience - Wohl, Ellen; Fryirs, Kirstie; Grabowski, Robert C.; Morrison, Ryan R.; Sear, David (Oxford University Press (OUP), 2024)
Resilience, which can also be described as absorbing capacity, describes the amount of change that a system can undergo in response to disturbance and maintain a characteristic, self-sustaining regime of functions, processes, or sets of feedback loops. Rivers exhibit varying levels of resilience, but the net effect of industrialized anthropogenic alteration has been to suppress river resilience. As changing climate alters the inputs to rivers and human modification alters the morphology and connectivity of rivers, restoration increasingly considers how to enhance resilience. Characteristics that underpin river absorbing capacity include natural regimes, connectivity, physical and ecological integrity, and heterogeneity. River management emphasizing channel stabilization and homogenization has reduced river absorbing capacity. We propose that the paths to restoring rivers include defining relevant measures of absorbing capacity and understanding the scales of restoration and the sociopolitical elements of river restoration. We provide a conceptual framing for choosing measures that could be used to assess river absorbing capacity.
Keywords: 4102 Ecological Applications; 41 Environmental Sciences; Ecology; 31 Biological sciences